Service Matters: Capital Misallocation and Sectoral Economic Growth - Woo Jin Choi; Woo Jin Roh (KDI Journal of Economic Policy, 2023)
Growth of the Korean economy has been sluggish, and this situation is more pronounced in the service sector. We argue that capital misallocation, especially in the service sector, could contribute to this slowdown. Utilizing firm and sectoral level data, first we assess the rising dispersion of the marginal revenue product of capital (MRPK) driven by the service sector. This could represent a widening misallocation of capital. Furthermore, a panel regression shows that within-sector misallocations at the sectoral level are closely correlated with the lower growth rate of sectoral real value added. Again, this is mainly observed in the service sector, but not in the manufacturing sector. Misallocations of other resources, labor and the intermediate inputs do not stand out.
Keywords: D24; O40; O41; O49; 330; Resource Misallocation; Firm-level Data; Sectoral Growth